Allelopathic Influence of Hortisilvicultural Tree Species on Arable Crops under Semi Arid Conditions - Hiwale, S.S.; Kakade, D.K.; Gohil, D.I.; Bagle, B.G.; Dhandhar, D.G. (Indian Journal of Agroforestry, 2020)
The experiment was carried out to study allelopathic effect of leaf leachate of four tree species viz., Custard apple (Annona squamosa), Aonla (Emblica officials), Neem (Azadirachta indica) and Subabool (Leucaena leucocephala) on Soybean (Glycin max), Maize (Zea mays), Okra (Abelmoschus esculentus), Sunhemp (Cratolaria juntia), Green gram (Phaseolus aurus), Pigeon pea (Cajanus cajan), Fodder jowar (Sorghum vulgare), Sesamum (Sesamum indicum) and Moth bean (Phaseolus aconitifolius). Seed germination was suppressed by leaf leachates of all tree species compared to control (seed treatment with distilled water). Observation on growth parameters indicated shoot and root length was significantly influenced by the leaf leachates of all the tree species. Root length was highly influenced compared to shoot length. Neem was found to suppress most of the growth parameters, whereas, Subabool, Custard apple and Aonla promoted them. Custard apple, Aonla and Subabool were found to have beneficial effect on Soya bean, Green gram, Pigeon pea and Sesamum and suppressing effect on Okra, Fodder jowar, Sunhemp, Maize and Moth bean.